Nursing work in care practice at Emergency Care Units - Cabreira Gehlen, Graciela; da Silva Lima, Maria Alice Dias (Investigación y Educación en Enfermería, 2013)
<!– [if gte mso 9]> <![endif]–> Objective. To characterize nurses’ work process in care practice at Emergency Care Units. Methodology. The research technique used was mixed-method research. In the quantitative phase, a questionnaire was applied to 47 nurses; in the qualitative phase, a sample of events was observed at an emergency unit. Results. The activities the nurses most frequently developed were: a) care: risk assessment and classification (66%) and registering of clinical data (62%); b) management: task distribution (62%), shift organization (40%) data processing (36%), and material provision (28%). The nurses highlighted the users’ forwarding to appropriate care levels as the goal of their work (70%). The work instruments most frequently used were clinical decision-making (87%), listening and monitoring (83%) and the risk assessment protocol (68%). Conclusion. Nurses’ work at Emergency Units is predominantly focused on care, with a great burden of management activities related to resource planning and provision for care practice.